The Physician and Sportsmedicine (The Physician and Sportsmedicine)
The Physician and Sportsmedicine is a peer-reviewed monthly journal serving the practicing physician's professional and personal interests in the medical aspects of exercise, sports, and fitness. The most widely read clinical sports medicine journal in the world, we cover practical, primary care-oriented topics such as diagnosing and treating knee and ankle injuries, managing chronic disease, preventing and managing overuse injuries, helping patients lose weight safely, and all manner of exercise and nutrition topics.